PEDAGOGICAL AND PSYCHOLOGICAL METHODS OF DEVELOPING PROFESSIONAL DEFORMATION IN FUTURE EDUCATORS (TAMADDUN NURI JURNALI, 2024)
This article is devoted to the scientific and practical studies of the improvement of professional development in higher educational institutions and the deformation (adaptation to work, getting used to) of relations and participants in the field of education.